OSCILLATION OF LINEAR NEUTRAL DIFFERENTIALEQUATION OF THIRD ORDER - Mohamad, Hussain (Iraqi Journal of Science, 2024)
In this paper sufficient conditions for oscillation of bounded and all solutions oflinear third order neutral delay differential equation are studied. Examples areinserted to illustrate the obtained results